Semantic Verbs Are Intensional Transitives. Issue 509 (21st December 2017) - D'Ambrosio, Justin
Abstract: In this paper I show that we have strong empirical and theoretical reasons to treat the verbs we use in our semantic theorizing—particularly 'refers (to)', 'applies (to)', and 'is true (of)'—as intensional transitive verbs (ITVs). Stating our semantic theories with intensional vocabulary allows us to partially reconcile two competing approaches to the nature and subject-matter of semantics: the Chomskian approach, on which semantics is non-relational, internalistic, and concerns the psychology of language users, and the Lewisian approach, on which semantics is fully relational, specifies truth-conditions, and has metaphysical implications. ITVs have two readings: an intensional, de dicto reading, and a relational, de re reading. A semantic theory stated with the de dicto readings of our semantic verbs captures the core insights of the Chomskian approach to semantics, in part because it allows us to assign extremely fine-grained semantic values to expressions, even when those expressions are empty. On the other hand, the de re reading yields a theory that is fully relational, and issues in truth-conditions. The resulting theories are related—and compatible—in that they are expressed by two different readings of the very same semantic vocabulary, and plausibly, the distinction between these two readings is one of scope.